Preparation of Poly(urea-formaldehyde) Microcapsules Containing Sulfur by in situ Polymerization - Li, J.; Wang, S.J.; Liu, H.Y.; You, L.; Wang, S.K. (Asian Journal of Chemistry, 2011)
Poly(urea-formaldehyde) microcapsules containing sulfur were prepared by in situ polymerization in a sulfur-in-water suspension. The two preparation steps of sulfur-water dispersion and coating process were investigated. Sedimentation experiments showed that the stability of the suspension decreased with an increase in the weight ratio of water and sulfur and the optimal adding amounts of sodium dodecyl sulfonate and gelatin were 0.7 and 7 wt % for maintaining the stability of the suspension. Scanning electron microscopy analysis showed that the mean diameter and size distribution of microcapsules were narrowed down with increasing the concentration of sodium dodecyl sulfonate and the emulsifying speed. The encapsulation test and morphology observation showed that poly(urea-formaldehyde) microcapsules with spherical shape and high encapsulation efficiency were achieved at pH 3, shell-core weight ratio of 2.0-2.5 and sodium dodecyl sulfonate concentration of 0.7 wt %.